Hepatitis C virus: discovery, cure and protection - Evans, Matthew (Henry Stewart Talks, 2020)
Basic molecular virology of the hepatitis C virus (HCV), Introduction to hepatitis viruses and HCV induced disease, The timeline of HCV discovery to cure, HCV structure, Treatment of HCV, HCV persistence and vaccine potential, Mechanisms that restrict HCV tropism to human livers